SAT0063 ASSOCIATION OF SMOKING WITH TRIPLE CONCORDANT SEROPOSITIVITY IN RA PATIENTS, AND WITH RHEUMATOID FACTOR IN THE REMAINING PATIENTS. (June 2019) - Regueiro, Cristina; Rodriguez, Luis Rodriguez; López-Mejías, Raquel; Nuño, Laura; Triguero-Martinez, Ana; Perez-Pampín, Eva; Corrales, Alfonso; Villalva, Alejandro; Lopez-Golan, Yolanda; Abasolo, Lydia; Martinez, Sara Remuzgo; Ortiz, Ana; et al.
Abstract : Background: The contribution of cigarette smoking to the risk of rheumatoid arthritis (RA) is larger for seropositive than for seronegative patients. Current pathogenic models explain this difference via the production of anti-citrullinated protein antibodies (ACPA) induced by protein citrullination in the lungs as a consequence of smoking. However, there are inconsistent results with this model including the van Wesemael et al . report, which found an association of smoking with the concurrent presence of ACPA, rheumatoid factor (RF) and anti-carbamylated protein antibodies (ACarPA), rather than with ACPA. Objectives: We aimed to explore the relationship between smoking and the presence of FR, ACPA and ACarPA and their combinations in patients with RA. Methods: Six cohorts with 2253 RA patients were obtained to replicate the van Wesemael et al . results. After replication, they were combined with the three cohorts from that study comprising 2238 patients to a total of 4491 patients. The results from the different cohorts were combined by fixed-effects meta-analysis. Most analyses involved comparisons between two levels of smoking exposure, never and ever smokers, considering the RF - /ACPA - /ACarP - patients as the reference. Results: Analysis of the replication set confirmed the predominant association of smoking with the concurrent presence of the three RA autoantibodies (OR = 1.99, P = 2.5 x 10 -8 ), whereas the patients with one or two antibodies were not different from the patients without antibodies (OR = 1.22, p = 0.4 and OR = 1.22, p = 0.3, respectively). The combined meta-analysis with all the cohorts clarified the dominant association of smoking with the triple concordant seropositivity (OR = 2.00, p = 4.4 x 10 -16 ). In contrast, there was no association with the patient bearing one autoantibody (OR = 1.12, p = 0.4), and an in-between association with the concurrent presence of two antibodies (OR = 1.26, p = 0.009). Moreover, the association with the presence of three antibodies was significantly larger than with two antibodies (OR = 1.54, p = 1.4 x 10 -6 ), whereas the association with the presence of two antibodies was not larger than with one autoantibody (OR = 1.11, p = 0.3). In the patients remaining after exclusion of the triple seropositive, the smokers were exclusively associated with the RF + (OR = 1.28, p = 0.03 and OR = 1.30, p = 0.004 in the double and single positive patients, respectively). This association was independent of the reference, either the triple seronegative (OR = 1.29, p = 0.001) or all the RF - patients (OR = 1.32, p = 0.0002). Conclusion: Smoking increases RA susceptibility by promoting pathways leading to the concurrent presence of the three RA autoantibodies and, in its defect, to the production of RF. These actions are not covered by current pathogenic models and suggest that smoking accelerates epitope spreading. Reference: [1] van Wesemael, et al. Arthritis Res Ther. 2016;18:285. Acknowledgement: Supported by grants PI17/01606 and RD16/0012/0014 of the Instituto de Salud Carlos III (Spain) that are partially financed by FEDER. Disclosure of Interests: Cristina Regueiro : None declared, Luis Rodriguez Rodriguez: None declared, Raquel López-Mejías: None declared, Laura Nuño: None declared, Ana Triguero-Martinez: None declared, Eva Perez-Pampín: None declared, Alfonso Corrales: None declared, Alejandro Villalva: None declared, Yolanda Lopez-Golan: None declared, Lydia Abasolo: None declared, Sara Remuzgo Martinez: None declared, Ana Ortiz: None declared, Eva Herranz: None declared, ANA MARTíNEZ-FEITO: None declared, Carmen Conde : None declared, ANTONIO MERA VARELA: None declared, Alejandro Balsa Grant/research support from: Abbvie, Pfizer, Novartis, BMS, Nordic, Sanofi, Consultant for: Abbvie, Pfizer, Novartis, BMS, Nordic, Sanofi, Sandoz, Lilly, Paid instructor for: Pfizer, Speakers bureau: Pfizer, Novartis, UCB, Nordic, Sanofi, Sandoz, Lilly, Isidoro González-Álvaro: None declared, Miguel A González-Gay Grant/research support from: Prof. MA Gonzalez-Gay received grants/research supports from Abbvie, MSD, Jansen and Roche., Speakers bureau: Consultation fees/participation in company sponsored speaker's bureau from Pfizer, Lilly, Sobi, Celgene, Novartis, Roche and Sanofi., Benjamin Fernandez: None declared, Antonio Gonzalez: None declared